2020
DOI: 10.1007/s11332-019-00615-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of stroboscopic visual training on eye–hand coordination

Abstract: Background Stroboscopic visual training (SVT) has been shown to improve cognitive skills and perceptual performance by carrying out events under situations of intermittent vision. Aims The aim of this study was to investigate whether an SVT training period could improve the eye-hand coordination (EHC) performance on a practiced task for a group of sports participants. Methods Sixty-two male participants were randomly assigned to either a strobe group (SG n = 31), or control group (CG n = 31). The method employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 41 publications
2
31
0
Order By: Relevance
“…Moreover, multiple-object tracking performance, which we related to peripheral vision earlier, was not improved with stroboscopic training. Other intervention studies have shown that stroboscopic training is rather linked to anticipatory tasks, 132,135 to other basic visual skills, 137 and to eye-hand coordination 137,138 but does not affect visual search performance 138 or the ability to catch balls 142 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, multiple-object tracking performance, which we related to peripheral vision earlier, was not improved with stroboscopic training. Other intervention studies have shown that stroboscopic training is rather linked to anticipatory tasks, 132,135 to other basic visual skills, 137 and to eye-hand coordination 137,138 but does not affect visual search performance 138 or the ability to catch balls 142 …”
Section: Resultsmentioning
confidence: 99%
“…The duration of interventions in the studies ranged from a few minutes 132,138 to that of an entire baseball season 72 . Short interventions can already lead to improvements, for example, in an anticipatory timing task 132 .…”
Section: Resultsmentioning
confidence: 99%
“…The importance of hand–eye coordination cannot be overemphasized in modern sports training [ 30 , 31 , 32 ]. Simply put, it is how well eyes are able to control the movement of hands, for instance, eyes send signals to the brain, which directs the movement of the hands.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond these values, an area of oscillation of the center of pressure with eyes closed greater than that obtained with eyes open indicates a visual dependence. To overcome this visual dependence, the use of stroboscopic glasses associated with visuomotor training has demonstrated its effectiveness in particular in reducing reaction time, in improving muscle coactivation, and through the phenomenon of anticipation, which then makes it possible to reduce the risk of injury, particularly the ACL [25][26][27][28][29][30][31]. The Star Excursion Balance Test or Y Balance Test constitutes a reliable means [31] of also being able to predict the risk of injury to the lower limb and a fortiori that of the ACL in footballers, in particular in the study by Lee et al (2015) who found a strong correlation with knee flexors and hip abductors [32].…”
Section: Biomechanicsmentioning
confidence: 99%